Let us stand with Julia! International Students or Immigrant Workers in the United States - Bista, Krishna (Journal of International Students, 2020)
Julia Iafrate, a Canadian-born immigrant medical doctor, who now works at Columbia University Irving Medical Center, shared her personal story with CNN’s Chris Cuomo that her green card was denied. She received the news of denial while she was treating critically ill coronavirus patients in the ICU in early May 2020. Julia earned all her medical degrees and credentials from American universities– Arizona College of Osteopathic Medicine, Mayo Clinic, and the University of Iowa Hospital & Clinics. She is one of millions of former international students or immigrant workers in the United States. Currently, there are more than 44,728,721 immigrants living and working in the United States. This short essay reviews the contributions of former international students or immigrants in the United States who have contributed significantly to U.S. health and medicine, science and technology, education and business, government and military, and job creation and innovation.